Aptitude and experience as predictors of grammatical proficiency in adult Greek-English bilinguals - Prela, Leonarda; Llompart, Miquel; Dabrowska, Ewa (Frontiers in Psychology, 2022)
It has been shown that individuals exhibit great variability in second language (L2) ultimate attainment. Some speakers reach native-like proficiency, others only achieve a rudimentary command and many lie in the middle. Individual differences research has partly attributed different degrees of L2 attainment to (language) aptitude. Initially considered irrelevant for first language (L1) acquisition, aptitude was viewed as a compensatory ability for adults' disadvantage in L2 learning. In this line of thought, adults and children are viewed as fundamentally different and rely on different language learning mechanisms. However, aptitude might not be so irrelevant for the L1. Together with input the two factors are found to account for individual differences not only in L2 but also L1 development. Recent research has specifically shown that native grammatical attainment may be modulated by aptitude and input. In this respect, the aim of the current study is to examine the effects of these two predictors (namely input and aptitude) on both L1 and L2 grammatical attainment in the same speakers. Our participants (N = 75) were all native speakers of Greek who learned English as a foreign language in their home country and immigrated to the United Kingdom in adulthood (mean age of arrival = 27.3, SD = 6.4). Grammatical proficiency was measured through a grammaticality judgement task administered in both the L1 and the L2. Aptitude was measured through the Sentence Pairs task (based on the Words In Sentences test from the MLAT battery). Amount of input was measured using the traditional measure, length of residence (LoR) and a new cumulative measure that spanned across the participants' life. The two measures were pitted against each other in the analysis. We found robust effects of aptitude in both the L1 and the L2, with the effect being even stronger for the L1. As expected, our new cumulative measure of exposure proved to be a better predictor of individual differences in grammatical proficiency. Last but not least, the effects of input were larger for the L2 than the L1.
CRIS-Team WoS Importer:2023-01-20

Beyond age: exploring ultimate attainment in heritage speakers and late L2 learners - Prela, Leonarda; Dabrowska, Ewa; Llompart Garcia, Miguel (Frontiers in Psychology, 2024)
According to the Critical Period Hypothesis, successful language learning is optimal during early childhood, whereas language learning outside of this time window is unsuccessful. In this respect, early language acquisition is viewed as convergent and reliable but late acquisition is not. The present study revisits the idea of a critical period by investigating the grammatical attainment of early bilinguals/heritage speakers (HSs), late second/foreign language (L2) learners, and comparable groups of monolinguals by testing Greek-English bilinguals in the two languages they speak by means of a grammaticality judgment task. Our findings show that in English, HSs performed on par with monolinguals, both groups surpassing the late L2 learners, who performed about 2 SDs below the HSs and the monolinguals. In Greek, late L2 learners and monolinguals exhibited comparable performance, contrasting sharply with the HSs’ significantly lower proficiency, which was on average about 5 SDs below the late L2 learners and the monolinguals. Consequently, our results show that the performance gaps between HSs and Greek monolinguals/late L2 learners were more pronounced than the differences between late L2 learners and English monolinguals/HSs, suggesting that the early bilinguals’ success in English may come at the expense of their heritage language (Greek). Furthermore, we observe substantially more individual variation within HSs in their heritage language than within the late L2 learners for their second language. Thus, testing bilinguals in both of their languages allows us to unveil the complexity of grammatical ultimate attainment and prompt a re-thinking of age as the major determining factor of (un)successful attainment.
CRIS-Team Scopus Importer:2024-08-30
Keywords: bilingualism; grammar; heritage language acquisition; late bilinguals; second language acquisition; ultimate attainment

The interplay of lexical and grammatical development in Greek-Albanian bilingual children: evidence from the majority and the heritage language - Kaltsa, Maria; Prentza, Alexandra; Prela, Leonarda; Tsimpli, Ianthi Maria (International Journal of Bilingual Education and Bilingualism, 2024)
The present paper aims to investigate the interplay of lexical and grammatical development in school-aged Greek-Albanian bilingual children by providing evidence both from majority, Greek, and heritage, Albanian. To this end, 47 8 to 10-year-old bilingual children were tested by means of expressive vocabulary tests in Greek and in Albanian, while their grammatical skills were evaluated by means of the LITMUS Sentence Repetition Task administered in both languages. Additionally, input-related measures in both languages, such as oral language practices, literacy, and educational practices were used to assess the bilingual experience and examine how it would correlate with lexical and grammatical skills. The analysis showed that within each language, lexical and grammatical skills were closely related both for the majority and the heritage language, while when examining across-language effects, grammatical skills in the heritage language were correlated with grammatical skills in the majority language. Concerning the role of input, we found that input in the heritage language supported skills both in the heritage and the majority language. The study's contribution is that by providing novel evidence from this specific language pair it shows that supporting the use of heritage language can boost language skills in both languages.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Albanian; child bilingualism; grammatical development; Greek; heritage language; lexicon; majority language